OPTIMALISASI NILAI-NILAI ISLAM PADA SISWA MADRASAH IBTIDIYAH MELALUI PEMBELAJARAN SEJARAH KEBUDAYAAN ISLAM - Munawir; Yaqin, Achmad Haqqul; Indana Hilyatun Nafisah; Alvina Rahmayanti; Faiqoh, Elok (PREMIERE : Journal of Islamic Elementary Education, 2023)
This Research has been carried out in the absense of the value of Islamic religion to student at learning Islamic history in the school. The generation of Muslim civilization is a Muslim youth who will succeed the nation which will be passed down from generation to generation and will continue the struggle of the previous fighters in realizing the desired nation's hopes. The existence of history, becomes a reminder of the services of the martyrs' struggle for martyrs' who died on the battlefield in defending Muslims and fighting for the religion of Islam with the intention of lillahi ta'ala and solely for the sake of Allah SWT. Notes and memories are collected in a sheet that becomes a guide for students in studying the cultural histories of earlier Muslims. Islamic students are required to be the next generation of Muslim civilization. Islamic students are a milestone in the generation of national civilization which will later advance the development of the Islamic religion, especially in the current millennial era which is increasingly sophisticated and technology is very fast so that there are many understandings that exist outside of Islam.